Community-based models of care for adolescent and adult depression, suicidal behavior, anxiety, trauma, and substance use in Africa: a scoping review - Raeber, Fabian; Haldemann, Maria-Inés; Ray, Somidha; Huber, Jacqueline; Firima, Emmanuel; Fernandez, Lucia Gonzalez; Amstutz, Alain; Gerber, Felix; Labhardt, Niklaus D.; Belus, Jennifer M. (Frontiers in Psychology, 2024)
Background: Community-based care (CBC), where care is delivered outside of the traditional health facility setting, has been proposed to narrow the mental health (MH) and substance use (SU) treatment gap in Africa. Objective: This scoping review aims to comprehensively summarize CBC models addressing adolescent and adult MH (depression, anxiety, trauma, suicidal behavior) and (non-tobacco) SU problems in Africa. Methods: We searched PsycINFO, Embase, Scopus, CINAHL, and Medline Ovid. Studies and protocols were included if they reported on CBC intervention's effects on MH or SU symptoms/ diagnoses, acceptability, feasibility, or patient engagement in care. Interventions wherein the content does not focus specifically on MH or SU were also included. Results: Among 11,477 screened publications, 217 were eligible. Of the unique intervention studies (n=206), CBC models were classified into the following approaches (non-mutually exclusive): psychotherapeutic (n=144), social (n=81), lifestyle/physical health (n=55), economic (n=26), and psychopharmacological (n=2). While quantitative results suggest possible efficacy of CBC models, description of location was often poor. Fewer interventions addressed suicidal behavior (n=12), the needs of adolescents (n=49), or used traditional healers or religious figures as providers (n=3). Conclusion: Many CBC models have been tested on MH and SU in Africa and should be critically appraised and analyzed in subsequent reviews.